Investigation of the guided-mode characteristics of hollow-core photonic band-gap fibre with interstitial holes - 苑金辉 余重秀 桑新柱 张锦龙 周桂耀 李曙光 侯蓝田 (Chinese physics B, 2011)
This paper investigates the guided-mode characteristics of hollow-core photonic band-gap fibre （HC-PBGF） with interstitial holes fabricated by an improved twice stack-and-draw technique at visible wavelengths. Based on the simulation model with interstitial holes, the influence of glass interstitial apexes on photonic band-gaps is discussed. The existing forms of guided-mode in part band gaps are shown by using the full-vector plane-wave method. In the experiment, the observed transmission spectrum corresponds to the part band gaps obtained by simulation. The fundamental and second-order guided-modes with mixture of yellow and green light are observed through choosing appropriate fibre length and adjusting coupling device. The loss mechanism of guided-modes in HC-PBGF is also discussed.